Organizational Identity: What is the Conversation Currently Dealing with? Paradigms, Perspectives, and Discussions - Gonzales-Miranda, Diego; Gentilin, Mariano; Ocampo-Salazar, Carmen (Pontificia Universidad Católica del Perú. CENTRUM, 2015)
This paper presents the results of a data research on the issue of organizational identity, the aim of which was to explore the current state of the discussion on organizational identity based on the analysis of papers published in 10 of the world’s leading organizational and management journals between 2000 and 2011, in order to identify paradigms, subjects, and trends. After a first selection of 5509 papers, 92 articles dealing with the specific issue of organizational identity were classified for analysis. Identity is not only an important perspective of study within the organizational field, but it has also become a relevant reference to bear in mind in order to understand phenomena related to organizations.
Keywords: Identity; Analysis perspectives; Organizational identity; Organizational identity paradigms; Organizational studies; https://purl.org/pe-repo/ocde/ford#5.02.04